The role of school activities in consolidating some educational principles among middle school students (Journal of the College of Basic Education, 2022)
The aim of the research is to know the role of school activities in consolidating some educational principles for middle school students, and to achieve the goal of the research, the researchers chose a sample for the research of Al-Jawahri Preparatory School for Boys intentionally, and the researchers prepared a questionnaire consisting of four axes based on literature and previous studies, which in its final form consisted of (44 Paragraph, and the tool was applied to the research sample and the data was statistically processed by the SPSS statistical bag and the (Excel) program to calculate a number of psychometric properties. The results of the research showed: the usefulness, reality and practice of school activities for students in a good percentage by students, in addition to the presence of many obstacles to the practice of these activities. In light of these results, the researchers developed a set of recommendations and suggested conducting subsequent studies to complement the research.